Vitamin A inhibits lipoperoxidation ascorbate-Fe⁺⁺ dependent of rat kidney microsomes and mitochondria - Piergiacomi, Viviana Angélica (1996)
In the present study it was investigated if Vitamin A supplementation could protect rat kidney microsomes and mitochondria from in vitro lipoperoxidation. After incubation of rat kidney microsomes and mitochondria in an ascorbate-Fe⁺⁺ system, at 37°C during 60 min, it was observed that the total cpm/mg protein originated from light emission (chemiluminescence) was lower in those organelles obtained from the control group when compared with the vitamin A supplemented group. The fatty acid composition of microsomes and mitochondria from control group was profoundly modified when subjected to nonenzymatic lipoperoxidation with a considerable decrease of arachidonic acid, C20:4 (n-6) and docosapentaenoic acid, C22:5 (n−3) in mitochondria and docosahexaenoic acid C22:6 (n-3) in microsomes.As a consequence the peroxidizability index, a parameter based on the maximal rate of oxidation of specific fatty acids was higher in the supplemented animals than in those used as control. These results indicate that Vitamin A may act as antioxidant protecting rat kidney microsomes and mitochondria from deleterious effect.